Japan : (Kodansha International, 1995)
Based on "Japan: An Illustrated Encyclopedia", this reference work contains over 200 articles organized into thematic sections on geography, history, government, economy, society, culture, and lifestyles of Japan and the Japanese. The articles in each category cover topics as diverse as corporate culture, women in the labour force, cram schools, karaoke, and comics, as well as international relations and foreign trade.